2022
DOI: 10.1109/tvcg.2022.3150491
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Direct and Indirect Methods of Audio Quality Evaluation in Virtual Reality Scenes of Varying Complexity

Abstract: Many quality evaluation methods are used to assess uni-modal audio or video content without considering perceptual, cognitive, and interactive aspects present in virtual reality (VR) settings. Consequently, little is known regarding the repercussions of the employed evaluation method, content, and subject behavior on the quality ratings in VR. This mixed between-and within-subjects study uses four subjective audio quality evaluation methods (viz. multiple-stimulus with and without reference for direct scaling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Additionally, audio-visual incongruence could impair cross-modal integration and thus lead to greater cognitive load [29]. Finally, scene complexity and interactivity in 6-DoF VR may impede quality judgments [30]. Thus, the experimental design must consider the interaction between the audio and visual stimuli and their degree of change between trials to minimize confounding factors.…”
Section: Visual Impact On the Perception Of Spatial Audiomentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, audio-visual incongruence could impair cross-modal integration and thus lead to greater cognitive load [29]. Finally, scene complexity and interactivity in 6-DoF VR may impede quality judgments [30]. Thus, the experimental design must consider the interaction between the audio and visual stimuli and their degree of change between trials to minimize confounding factors.…”
Section: Visual Impact On the Perception Of Spatial Audiomentioning
confidence: 99%
“…The order of removal corresponds to the participant's ranking of the stimuli. Robotham et al recommend using this method in multi-modal 6-DoF VR and reference-free testing due to its efficiency, mental demand and participant effort compared to MSHR (multiple stimuli, hidden reference) methods [30].…”
Section: Testing Of Participants In 6-dof Vrmentioning
confidence: 99%
See 1 more Smart Citation
“…bringing real life into laboratory experiments, as pointed out by [161]. Indeed, with VR tools, it is possible to synthesize a wide range of environments, while precisely controlling experimental parameters and combining multiple sensory inputs [165]. For instance, the audio modality can be completed by visual, proprioception and vestibular cues.…”
Section: Ecological Validity Of Assessmentmentioning
confidence: 99%
“…New tools have been developed to perform listening tests and behavioral studies in interactive virtual environments [78]. In a recent study, various direct and indirect audio quality evaluation methods were compared in virtual reality scenes of varying complexity [79]. It was found that rank-order elimination proved to be the fastest method, required the least amount of repetitive motion, and yielded the highest discrimination between spatial conditions.…”
Section: Perception and Evaluationmentioning
confidence: 99%